On Decomposable Measures Induced by Metrics. (2nd July 2012) - Qiu, Dong; Zhang, Weiquan
Abstract : We prove that for a given normalized compact metric space it can induce aσ -max-superdecomposable measure, by constructing a Hausdorff pseudometric on its power set. We also prove that the restriction of this set function to the algebra of all measurable sets is aσ -max-decomposable measure. Finally we conclude this paper with two open problems.